2020
DOI: 10.1371/journal.pone.0243122
|View full text |Cite
|
Sign up to set email alerts
|

Can the detection dog alert on COVID-19 positive persons by sniffing axillary sweat samples? A proof-of-concept study

Abstract: The aim of this proof-of-concept study was to evaluate if trained dogs could discriminate between sweat samples from symptomatic COVID-19 positive individuals (SARS-CoV-2 PCR positive) and those from asymptomatic COVID-19 negative individuals. The study was conducted at 2 sites (Paris, France, and Beirut, Lebanon), followed the same training and testing protocols, and involved six detection dogs (three explosive detection dogs, one search and rescue dog, and two colon cancer detection dogs). A total of 177 ind… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
119
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(132 citation statements)
references
References 58 publications
10
119
0
3
Order By: Relevance
“…It does, however, reiterate the point raised by Edwards et al [ 23 ], that confirmed negative samples are critical. Grandjean et al [ 14 ] had a similar issue, with two of their supposed SARS-CoV-2 negative controls turned out to be positive, once they contacted the hospitals after the dogs signalled that they believed the samples were positive. With SARS-CoV-2, the false negative test rate of RT-PCR testing [ 11 ] and unknown duration of a signature odor after recovering from COVID-19, further complicate the procurement of control samples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It does, however, reiterate the point raised by Edwards et al [ 23 ], that confirmed negative samples are critical. Grandjean et al [ 14 ] had a similar issue, with two of their supposed SARS-CoV-2 negative controls turned out to be positive, once they contacted the hospitals after the dogs signalled that they believed the samples were positive. With SARS-CoV-2, the false negative test rate of RT-PCR testing [ 11 ] and unknown duration of a signature odor after recovering from COVID-19, further complicate the procurement of control samples.…”
Section: Discussionmentioning
confidence: 99%
“…Dogs are able to detect VOC signatures specific to a disease from different biological fluids including urine [ 11 ] and saliva [ 12 ]. To date, there is strong evidence that there is a unique VOC profile associated with SARS-CoV-2 infection and dogs can be trained to recognize it from saliva/tracheal samples [ 13 ] and sweat samples [ 14 ]. Jendrny et al [ 13 ] trained eight detection dogs over one week to discriminate between SARS-CoV-2 positive and negative saliva and tracheal secretion samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clostridium difficile or mastitis causing pathogens 16,17 , hypoglycaemia in diabetics 18 , and virus infections in cell cultures 12,19 . In addition, several research groups worldwide currently train and deploy SARS-CoV-2 detection dogs 20,21 . In a pilot study, our group showed that dogs were able to detect inactivated saliva samples from COVID-19 patients with a sensitivity of 83% and specificity of 96% 22 , which has been confirmed by other groups training dogs to detect either respiratory secretions or sweat samples from COVID-19 patients 20,21 .…”
Section: Odour Detectionmentioning
confidence: 99%
“…In addition, several research groups worldwide currently train and deploy SARS-CoV-2 detection dogs 20,21 . In a pilot study, our group showed that dogs were able to detect inactivated saliva samples from COVID-19 patients with a sensitivity of 83% and specificity of 96% 22 , which has been confirmed by other groups training dogs to detect either respiratory secretions or sweat samples from COVID-19 patients 20,21 . Despite these preliminary promising results, it remains to be shown whether dogs detect VOCs which are biofluid-specific or alternatively there is a more general change in odour of COVID-19 patients.…”
Section: Odour Detectionmentioning
confidence: 99%